Sex Commonalities and Differences in Obesity‐Related Alterations in Intrinsic Brain Activity and Connectivity. Issue 2 (27th December 2017) - Gupta, Arpana; Mayer, Emeran A.; Labus, Jennifer S.; Bhatt, Ravi R.; Ju, Tiffany; Love, Aubrey; Bal, Amanat; Tillisch, Kirsten; Naliboff, Bruce; Sanmiguel, Claudia P.; Kilpatrick, Lisa A.
Abstract : Objective: This study aimed to characterize obesity‐related sex differences in the intrinsic activity and connectivity of the brain's reward networks. Methods: Eighty‐six women ( n  = 43) and men ( n  = 43) completed a 10‐minute resting functional magnetic resonance imaging scan. Sex differences and commonalities in BMI‐related frequency power distribution and reward seed‐based connectivity were investigated by using partial least squares analysis. Results: For whole‐brain activity in both men and women, increased BMI was associated with increased slow‐5 activity in the left globus pallidus (GP) and substantia nigra. In women only, increased BMI was associated with increased slow‐4 activity in the right GP and bilateral putamen. For seed‐based connectivity in women, increased BMI was associated with reduced slow‐5 connectivity between the left GP and putamen and the emotion and cortical regulation regions, but in men, increased BMI was associated with increased connectivity with the medial frontal cortex. In both men and women, increased BMI was associated with increased slow‐4 connectivity between the right GP and bilateral putamen and the emotion regulation and sensorimotor‐related regions. Conclusions: The stronger relationship between increased BMI and decreased connectivity of core reward network components with cortical and emotion regulation regions in women may be related to the greater prevalence of emotional eating. The present findings suggest the importance of personalized treatments for obesity that consider the sex of the affected individual.